Analisis Perbedaan Tindakan Swafoto (Selfie) Dan Kepuasan Konsumen Generasi X Dan Generasi Z Pada Restoran Di Tangerang Selatan - Tito Siswanto; Asriyal Asriyal (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2019)
This research was conducted in South Tangerang City, involving generation X consumers born between 1960 and 1980, and generation Z consumers born between 1995-2010. The purpose of this research was to study differences in consumer satisfaction expressed through selfie photographs. The research involved 20 people from generation X and 20 people from generation Z. It is known that the selfies taken by consumers are a satisfaction for the service provided by the restaurant. This behavior occurs in the cross-generation, both generation X and generation Z. Satisfaction expressed through this selfie photo is shaped by brand image factors, comfort, characteristics, and ways of serving food. No difference in influence is known due to technological and information developments, as well as the widespread use of social media. Customers are encouraged to document the best moments and collected to build existence.